ANALISA PENTINGNYA PERAWATAN INJEKTOR DALAM RANGKA PENINGKATAN KINERJA GENERATOR DI KAPAL GAS AURORA - Nando Pearl Patasik; Sarifuddin; Rahmat Hidayat (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was conducted to examine the factors that cause injector leaks and their impact on the performance of generators powered by Yanmar S165L 6-cylinder auxiliary engines on the Gas Aurora vessel. The research approach used was a descriptive qualitative and ex post facto method, with information collected through field observations, engine operating parameter measurements, injector physical condition inspections, testing using test bench equipment, and interviews with engine personnel. The research findings indicate that injector leaks are triggered by a combination of mechanical, operational, and maintenance factors. The dominant triggers include nozzle and needle wear, sealing component failure, and carbon deposits due to prolonged low-load engine operation. Furthermore, the suboptimal implementation of the Planned Maintenance System (PMS) increases the risk of these problems. This situation results in an exhaust gas temperature (EGT) difference between cylinders of 20–40°C, increased fuel consumption, the appearance of exhaust smoke, and reduced generator performance stability during operation.